ANALISIS KEPUASAN ANGGOTA KOPERASI TERHADAP KUALITAS PELAYANAN PADA KOPERASI CREDIT UNION SUMBER SEJAHTERA KALIMANTAN SELATAN - Isra Ul Huda; Jhony Fahrin Sapar (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Cooperative which means a joint venture (Anoraga and Widiyanti, 1997:38-39). Cooperatives are people's economic institutions that encourage the people's economy to increase people's prosperity. Therefore, the focus of cooperatives is not only on products and services but also on their production, human resources, and the environment. Member satisfaction is the main factor that can make switching to another financial institution. Member satisfaction is one of the main goals of every institution. In this case, an important factor contributing to member satisfaction is service quality, which is recognized as the most important factor in member satisfaction. Member satisfaction depends on the quality of service desired. Based on the background of the problem, the formulation of the research problem is How is the Analysis of Cooperative Member Satisfaction on Service Quality at the Sumber Sejahtera Credit Union Cooperative, South Kalimantan?. The purpose of this study is to determine the satisfaction of cooperative members on service quality at the Sumber Sejahtera Credit Union Cooperative, South Kalimantan. The type of research used by the researcher is descriptive qualitative. According to Sugiyono (2016: 9) qualitative research methods are research methods used to examine the condition of natural objects where the researcher is the key instrument. In this study, the author uses an analytical technique, namely the customer satisfaction index (CSI). And the technique used in data collection is a questionnaire. The feasibility and reliability of the questionnaire will be measured using the validity and reliability test of the questionnaire, which data collection is online using the google form media. The study entitled "ANALYSIS OF COOPERATIVE MEMBERS' SATISFACTION ON SERVICE QUALITY IN CREDIT UNION SUMBER SEJAHTERA, SOUTH KALIMANTAN" concluded that service quality has a significant effect on member satisfaction. From the research conducted, the implementation of service quality in the majority of Credit Union cooperatives has been carried out well and in accordance with the wishes and needs of consumers. It is evident that the average respondent gives a high score on the scale of the answers provided. However, there are several elements that need to be considered by the company to be able to create consistency in customer satisfaction, such as increasing the parking area and improving sanitation and maintaining clean and fragrant toilets.